Can AI Personalize Treatment Recommendations? - Rasit, Dinc (Rasit Dinc Digital Health & AI Research, 2016)
The concept of personalized medicine, which involves tailoring medical treatments to the unique characteristics of each patient, is no longer a futuristic vi...
Keywords: AI in Clinical Decision Support; Personalize; Treatment; Recommendations; Artificial Intelligence; Machine Learning; Deep Learning